2014
DOI: 10.1039/c4ra06883a
|View full text |Cite
|
Sign up to set email alerts
|

Zinc selenide nano- and microspheres via microwave-assisted ionothermal synthesis

Abstract: Zinc selenide nanospheres were prepared from a diphenyl diselenide precursor and halozincate(ii) ionic liquids via a microwave-assisted ionothermal route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…We first attempted the controlled synthesis of sulfides of main group and transition metals starting from the elements. As IL, [P 66614 ]Cl was chosen because the commercially available product can be purified 10 and it had already demonstrated good solvent properties in the synthesis of metal phosphides, 8 selenides, 14,53–55 and tellurides. 10 The following elements were tested: B, Bi, Ge, Mo, Cu, Au, Sn, In, Ti, V, Fe, Co, Ga, Ni, Al, Zn, Sb.…”
Section: Resultsmentioning
confidence: 99%
“…We first attempted the controlled synthesis of sulfides of main group and transition metals starting from the elements. As IL, [P 66614 ]Cl was chosen because the commercially available product can be purified 10 and it had already demonstrated good solvent properties in the synthesis of metal phosphides, 8 selenides, 14,53–55 and tellurides. 10 The following elements were tested: B, Bi, Ge, Mo, Cu, Au, Sn, In, Ti, V, Fe, Co, Ga, Ni, Al, Zn, Sb.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, cobalt selenide (CoSe) is one of the best TMCs, because Co has good electrochemical properties while Se has a lower electronegative than other chalcogen and this combination will provide more reactive sites for the redox process and improve the efficiency of solar cells. Methods such as hot injection method, 35 microwave radiation method, 36 hydrothermal method, 37 and so on apply to prepare of CoSe. Among these, a hydrothermal method is highly preferable because of its easy procedure, large‐scale synthesis, highly reactive even in low‐temperature sintering, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metals such as Co, Zn, and many others have also been used to obtain metal-containing ILs. Lin et al have reviewed some of these metal-containing ILs with imidazolium used as cation . Another example of metal-containing ILs is deep-eutectic-solvents with metals incorporated as anions or cations, first introduced by Abbott et al Yoshida et al reported in 2005 room-temperature (RT) ILs containing iron­(III) ions based on 1-ethyl-3-methylimidazolium cations.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic properties of these compounds were investigated and single ion magnet behaviour at low temperatures was observed. A series of eleven new rare-earth-containing ionic liquids based on [La(NO 3 ) 6 ] 3-were reported by Ji et al 26 The ionic liquids have the composition ([C n Mim] 3 [La(NO 3 ) 6 ] (n = 1, 2, 4, 6,8,12,14,16,18). These ILs are water-free, which avoids issues with luminescence quenching.…”
mentioning
confidence: 95%
See 1 more Smart Citation